Effectiveness of introducing point of care capillary testing and linking screening with routine appointments for increasing blood lead screening rates of young children: a before-after study. Issue 1 (December 2015) - Boreland, Frances; Lyle, David; Brown, Anthony; Perkins, David
Abstract Background Lead has significant neuro-toxic effects, particularly for young children. Voluntary screening of pre-school aged children for elevated blood lead levels has been an important part of the lead management program in the mining town of Broken Hill (NSW, Australia) since 1991, where lead remains a significant public health issue for young children despite average blood lead levels having fallen by two-thirds. The annual proportion of children screened declined to 0.39 in 2008. The objective of this study was to determine the impact of changing to capillary screening and linking screening with existing routine health programs on participation in blood lead screening by young children in the community. Methods We used a before-after study. Screening rates were determined from routinely collected service data and analysed using cross-sectional and cohort analyses. Results The proportion of children screened annually increased from 0.39 in 2008 to 0.75 in 2012, with the greatest increases among 11–23 and 48–59 month old children. The proportion of children screened at least once by 24 months increased from 0.63 for children born in 2007 to 0.98 for children born in 2010. Attendance stabilized after capillary screening was introduced, and increased markedly after screening was offered at immunization. Conclusons Changing from venous to capillary screening stabilized attendance and improving convenience was associated with dramatically increased screening. Linking screening with well-accepted mainstream child health programs is an effective strategy to improve participation in blood lead screening programs. The findings have implications for improving participation in other health screening programs.